Spatial distribution, ecological and health risk assessment and source identification of atrazine in Shadegan international wetland, Iran. (November 2020) - Almasi, Halime; Takdastan, Afshin; Jaafarzadeh, Nematollah; Babaei, Ali Akbar; Tahmasebi Birgani, Yaser; Cheraghian, Bahman; Saki, Amal; Jorfi, Sahand
Abstract: Recently, atrazine has been increasingly used to control weeds in the corn and sugarcane farms, which affects the water resources and aquatic organisms. In this study, atrazine residual concentrations in water and fish samples of the Shadegan wetland (Iran) were investigated. Furthermore, the health and ecological risk assessment were calculated. A total of fifty water samples were collected from the wetland during three periods with a four-month time interval. Also, ten samples of ten different fish species were analyzed at the same time. The estimation of acceptable daily intake and comparison with international standards indicates danger to adjacent residential areas of wetland. Non-carcinogenic risk analysis showed that total hazard quotient (HQing + HQderm) were below the acceptable limit and there is no danger to the residents of the area. Atrazine concentration in the water and fish samples ranged between 0 and 2175.8 μg/L, and 0 to 35.58 μg/L, respectively. Results showed that 88% of the water samples were higher than EPA and WHO guidelines for drinking water in summer. The concentrations of atrazine in fish samples in summer were more than other seasons. Analysis of ecological risk assessment also showed that considering the average atrazine concentration in three seasons, the risk exposure was very high. This study will be beneficial to the both residents and government officials in management of Shadegan wetland pollution in term of toxic compounds. Graphical abstract: Unlabelled Image Highlights: Atrazine concentration was monitored in waster body and fishes living in Shadegan international wetland in southwestern of Iran. Carcinogenic and non-carcinogenic risks as well as ecological risk were assessed. Results showed that the atrazine concentration was more than standard in all sampling stations. Results indicated a risk of atrazine carcinogenicity for adults and children by water exposure, but non for dietary exposure.